The Use of Authentic Materials in Enhancing Students’ Listening Comprehension - Yayu Sri Rahayu (Journal of English Education Program (JEEP), 2015)
This study investigates the use of authentic materials in listening comprehension. Listening plays an important role in language learning. Therefore, in teaching listening there should contain real language that is used in the real life. In this regard, three questions are addressed: 1) How do the lecturers implement authentic materials in teaching listening comprehension?, 2) What kinds of authentic materials used by the lecturers in teaching listening comprehension?, and 3) What are the students’ perception on the use of authentic materials in listening comprehension?. The data were collected through several instruments, including classroom observation, interview to two listening lecturers and the writer administered questionnaires to two listening classes at the second grade in English Education Program of Galuh University in Ciamis. The findings revealed that the lecturers implement authentic materials in pre-, whilst-, and post-listening. The lecturers use authentic-listening viewing materials. However from the result of interview the lecturer 1 sometimes uses authentic-printed materials. Moreover, most of the students enjoyed and are interested in learning listening by using authentic materials. Keywords: Authentic materials, listening comprehension, students’ perception